Role and Relevance of Mast Cells in Fungal Infections - Saluja, Rohit; Metz, Martin; Maurer, Marcus (Frontiers in Immunology, 2012)
In addition to their detrimental role in allergic diseases, mast cells (MCs) are well known to be important cells of the innate immune system. In the last decade, they have been shown to contribute significantly to optimal host defense against numerous pathogens including parasites, bacteria, and viruses. The contribution of MCs to the immune responses in fungal infections, however, is largely unknown. In this review, we first discuss key features of mast cell responses to pathogens in general and then summarize the current knowledge on the function of MCs in the defense against fungal pathogens. We especially focus on the potential and proven mechanisms by which MC can detect fungal infections and on possible MC effector mechanisms in protecting from fungal infections.